Photonic crystal fiber refractive index sensor based on a fiber Bragg grating demodulation - Qian, Wenwen (2013)
A refractive index (RI) sensor is proposed which consists of a combination of an intermodal photonic crystal fiber (PCF) interferometer as a sensing head and a fiber Bragg grating (FBG) as a demodulating element. The intermodal PCF interferometer is formed by using a short PCF which is spliced with two single-mode fibers (SMFs) at both ends. The air-holes in the splice regions are fully collapsed and it forms the intermodal PCF interferometer. The corresponding interference phenomenon is found to be sensitive to the change of external RI. A FBG is connected serially after the intermodal PCF interferometer which is used to reflect the optical power at the Bragg wavelength of the interference transmission spectrum. With different external RI values, the corresponding reflective power of the FBG will change, which is resulted from the shift on the interference spectrum of the intermodal PCF interferometer. The resolution of the proposed RI sensor can be obtained as high as 1.5 × 10−5 at around RI of 1.360 with a combination of a 2.5 cm length intermodal PCF interferometer and a FBG at 1566.8 nm with 99% reflectivity. Due to a temperature compensation between the FBG and the intermodal PCF interferometer, the proposed RI sensor has a low temperature sensitivity and it is suitable for practical applications.